The Drinking Effect of Hydrogen Water on Atopic Dermatitis Induced by Dermatophagoides farinae Allergen in NC/Nga Mice - Ignacio, Rosa Mistica C. (Hindawi Publishing Corporation, 2013)
Hydrogen water (HW) produced by electrolysis of water has characteristics of extremely low oxidation-reduction potential (ORP) value and high dissolved hydrogen (DH). It has been proved to have various beneficial effects including antioxidant and anti-inflammatory effects; however, HW effect on atopic dermatitis (AD), an inflammatory skin disorder, is poorly documented. In the present study, we examined the immunological effect of drinking HW on Dermatophagoides farinae-induced AD-like skin in NC/Nga mice. Mice were administered with HW and purified water (PW) for 25 days. We evaluated the serum concentration of pro-inflammatory (TNF-α), Th1 (IFN-γ, IL-2, and IL-12p70), Th2 (IL-4, IL-5, and IL-10), and cytokine expressed by both subsets (GM-CSF) to assess their possible relationship to the severity of AD. The serum levels of cytokines such as IL-10, TNF-α, IL-12p70, and GM-CSF of mice administered with HW was significantly reduced as compared to PW group. The results suggest that HW affects allergic contact dermatitis through modulation of Th1 and Th2 responses in NC/Nga mice. This is the first note on the drinking effect of HW on AD, clinically implying a promising potential remedy for treatment of AD.